IMPLEMENTASI DAN ANALISIS PENGGUNAAN DD-WRT FIRMWARE UNTUK MEMBANGUN JARINGAN WIRELESS DISTRIBUTION SYSTEM PADA JARINGAN HOTSPOT (STUDI KASUS: FTI UKSW) - Wiwin Sulistyo; Teguh Indra Bayu; Achmad Sathibi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2012)
Wireless Distribution System allows for creating a wireless network without using a wired network backbone. Wireless network using WDS technology associated by create a link on some wireless access point that is called WDS links. The advantage by using WDS technology is to integrate all access points in a single wireless network. Wireless distribution system can handle the complexity of the cable instalation, where physically impossible to pull the cable as a backbone network. Wireless network using WDS technology has the mobility and high reliability. However, not all access points support WDS technology. Access points that use indoor access point that is WRT54GL which does not have WDS feature, because the standard firmware of access points it is still very less features. This problem can be solved by installing DD-WRT firmware into access point. after performing a firmware upgrade, the capability of the access points increase and has full features such as WDS feature.